Teacher’s Digital Capability Improvements of Miftahul Ulum Surabaya Junior High School Through Training Utilization of Google Apps - A. Faroqi; Suryanto, T. L. M.; R. Hadiwiyanti (Nusantara Science and Technology Proceedings)
The development of information technology and the internet is happening very rapidly, causing various jobs in various sectors to be passed on the internet. These developments are now progressing rapidly with the development of mobile technology. Now someone accessing the internet can be anywhere and anytime, does not have to sit facing the computer. From the rapid development of mobile technology, the Android operating system has become one of the operating systems on the most widely used. Android itself is an operating system created by Google, therefore for someone who has a smart phone based on the Android operating system, to be able to use it must have a google account. The majority of people have not realized that when he has a Google account, he can actually use various Google applications for free. This is evident from the condition of the teachers at Miftahul Ulum Surabaya Junior High School. The impact of this is the use of Android smartphones is not optimal, even though some Google applications are very useful to support administrative performance and teaching or learning in schools. The purpose of training the use of this google application is to provide increased knowledge and skills of teachers and administrative officers in the field of information technology, especially the use of google applications to support their daily tasks. In this activity, as many as twenty-seven teachers attended and participated in the training actively and enthusiastically.